Simultaneous confocal scanning laser fluorescein and indocyanine green angiography - Holz, Frank G.; Bellmann, Caren; Rohrschneider, Klaus; Burk, Reinhard; Völcker, Hans Eberhard (American journal of ophthalmology, 1998)
Purpose - To evaluate clinically a recently developed confocal scanning laser ophthalmoscope for simultaneous fluorescein and indocyanine green angiography. - Methods - After comprehensive ophthalmic examination, including stereoscopic biomicroscopy, and after color fundus photographs, simultaneous confocal scanning laser fluorescein and indocyanine green angiography was performed after injection of 500 mg of fluorescein and 25 mg of indocyanine green mixed in one syringe using the Heidelberg Retina Angiograph. An argon laser beam (488 nm) and a diodce laser beam (795 nm) from an external source were delivered by single-mode fibers. Emission was recorded between 500 and 700 nm and above 810 nm, respectively. Digital images were displayed simultaneously on a monitor during angiography. - Results - Two hundred twenty simultaneous fluorescein and indocyanine green angiograms were obtained in 193 consecutive patients with various diagnoses, including exudative age-related macular degeneration with occult and classic choroidal neovascularization. Simultaneous angiography with both dyes gave high-contrast images during all phases of the angiography, which allowed for accurate correlation of fluorescein and indocyanine green angiographic findings and correct comparison of the transit of both dyes through the retinal and choroidal circulation. Corresponding display of quasisimultaneous frames facilitated interpretation of the angiograms. - Conclusions - Confocal laser scanning angiography allows for quasisimultaneous fluorescein and indocyanine green angiography. The investigation is possible at low retinal irradiance and offers high-contrast digital images. Compared with consecutive angiographic investigations using both dyes, simultaneous angiography is less time consuming, requires only one injection, and, because quasisimultaneous frames are obtained, facilitates interpretation of the angiograms.
Elektronische Reproduktion der Druck-Ausgabe 6. Dezember 2002
Gesehen am 08.07.2024